IbM Inovasi Pengolahan Balakka - Produk Unggulan Desa Padang Garugur di Kabupaten Padang Lawas Utara - Lubis, Januardi Rosyidi; Tanjung, Akhir Abadi; Feri Irawan; Lubis, Mustopa Husein; Siregar, Selamat Riadi (Universitas Widya Mataram, 2024)
Padang Garugur Village in North Padang Lawas Regency has significant economic potential in agriculture and plantations, especially in processing balakka fruit. However,the problems faced include limited infrastructure, lack of product innovation, and low community skills in processing and marketing. To overcome this, community empowerment is needed through training and mentoring that focuses on product innovation, skills development, and digital marketing. The results of this activity show that the development of new products such as Balakka Coffee and Manisan Balakka is able to increase competitiveness and community income. The implementation of effective marketing strategies through social media and digital platforms has successfully expanded market reach. In conclusion, innovation and community capacity building can improve the welfare and economic growth of the village. With a systematic and collaborative empowerment approach, Padang Garugur Village can become a model of sustainable local wisdom-based community empowerment